Demographic, socio-economic, obstetric, and behavioral factors associated with small-and large-for-gestational-age from a prospective, population-based pregnancy cohort in rural Nepal: a secondary data analysis - Hazel, Elizabeth A.; Mohan, Diwakar; Zeger, Scott; Mullany, Luke C.; Tielsch, James M.; Khatry, Subarna K.; Subedi, Seema; LeClerq, Steven C.; Black, Robert E.; Katz, Joanne (BMC pregnancy and childbirth, 2022)
Background In South Asia, a third of babies are born small-for-gestational age (SGA). The risk factors are well described in the literature, but many studies are in high-and-middle income countries or measure SGA on facility births only. There are fewer studies that describe the prevalence of risk factors for large-for-gestational age (LGA) in low-income countries. We aim to describe the factors associated with SGA and LGA in a population-based cohort of pregnant women in rural Nepal. Methods This is a secondary data analysis of community-based trial on neonatal oil massage (22,545 women contributing 39,479 pregnancies). Demographic, socio-economic status (SES), medical/obstetric history, and timing of last menstruation were collected at enrollment. Vital signs, illness symptoms, and antenatal care (ANC) attendance were collected throughout the pregnancy and neonatal weight was measured for live births. We conducted multivariate analysis using multinomial, multilevel logistic regression, reporting the odds ratio (OR) with 95% confidence intervals (CIs). Outcomes were SGA, LGA compared to appropriate-for-gestational age (AGA) and were multiply imputed using birthweight recalibrated to time at delivery. Results SGA was associated with nulligravida (OR: 2.12 95% CI: 1.93–2.34), gravida/nulliparous (OR: 1.86, 95% CI: 1.26–2.74), interpregnancy intervals less than 18 months (OR: 1.16, 95% CI: 1.07–1.27), and poor appetite/vomiting in the second trimester, (OR: 1.27, 95% CI: 1.19–1.35). Greater wealth (OR: 0.78, 95% CI: 0.69–0.88), swelling of hands/face in the third trimester (OR: 0.81, 95% CI: 0.69–0.94) parity greater than five (OR: 0.77, 95% CI: 0.65–0.92), male fetal sex (OR: 0.91, 95% CI: 0.86–0.98), and increased weight gain (OR: 0.93 per weight kilogram difference between 2 nd and 3 rd trimester, 95% CI: 0.92–0.95) were protective for SGA. Four or more ANC visits (OR: 0.53, 95% CI: 0.41–0.68) and respiratory symptoms in the third trimester (OR: 0.67, 95% CI: 0.54–0.84) were negatively associated with LGA, and maternal age < 18 years (OR: 1.39, 95% CI: 1.03–1.87) and respiratory symptoms in the second trimester (OR: 1.27, 95% CI: 1.07–1.51) were positively associated with LGA. Conclusions Our findings are in line with known risk factors for SGA. Because the prevalence and mortality risk of LGA babies is low in this population, it is likely LGA status does not indicate underlaying illness. Improved and equitable access to high quality antenatal care, monitoring for appropriate gestational weight gain and increased monitoring of women with high-risk pregnancies may reduce prevalence and improve outcomes of SGA babies. Trial Registration The study used in this secondary data analysis was registered at Clinicaltrials.gov NCT01177111.